2019
DOI: 10.3389/fpsyt.2019.00910
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoyaosan Ameliorates Chronic Immobilization Stress-Induced Depression-Like Behaviors and Anorexia in Rats: The Role of the Nesfatin-1–Oxytocin–Proopiomelanocortin Neural Pathway in the Hypothalamus

Abstract: Background: Chronic stress is an important risk factor for depression. The nesfatin-1 (NES1)-oxytocin (OT)-proopiomelanocortin (POMC) neural pathway, which is involved in the stress response, was recently shown to have an anorectic effect in the hypothalamus. Our previous study showed that Xiaoyaosan, a well-known antidepressant used in traditional Chinese medicine, effectively relieved appetite loss induced by chronic immobilization stress (CIS). However, whether Xiaoyaosan ameliorates depression-like behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The two-way regulatory effect of Xiaoyaosan on depression and anxiety has been previously reported. For example, Xiaoyaosan can exert anxiolytic effects through the CRF1 receptor (Jiang et al, 2016) and the JNK signaling pathway (Zhao et al, 2017) and can improve depressive behavior by targeting the Nesfatin-1 receptor (Ma et al, 2019). Our current research confirmed the two-way regulation of anxiety and depression by Xiaoyaosan could be attributed to the alteration in the abundance of intestinal flora and reduction in endotoxin-induced inflammation.…”
Section: Discussionsupporting
confidence: 72%
“…The two-way regulatory effect of Xiaoyaosan on depression and anxiety has been previously reported. For example, Xiaoyaosan can exert anxiolytic effects through the CRF1 receptor (Jiang et al, 2016) and the JNK signaling pathway (Zhao et al, 2017) and can improve depressive behavior by targeting the Nesfatin-1 receptor (Ma et al, 2019). Our current research confirmed the two-way regulation of anxiety and depression by Xiaoyaosan could be attributed to the alteration in the abundance of intestinal flora and reduction in endotoxin-induced inflammation.…”
Section: Discussionsupporting
confidence: 72%
“…The OFT was conducted as previously described (Ma et al, 2019). An open field box (100 cm × 100 cm × 50 cm) with a black floor and four black sidewalls was placed in the middle of a dark and quiet operation room, and a video camera connected to a computer was placed 1.5 m above the middle of the box.…”
Section: Behavioral Testing Open Field Testmentioning
confidence: 99%
“…The SPT was carried out on day 0 (as baseline), day 21 and day 41 of the experimental process according to previously described methods (Ma et al, 2019). Briefly, the rats were deprived of food and water before the SPT.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…At present, the etiology of GAD is unclear, but it is certain that environmental pressure is an important reason for its onset, repeated fluctuation, and deterioration ( Wittchen et al, 2000 ). Based on this, this study used the uncertain empty bottle drinking water stimulation method ( Lin Wenjuan, 2003 ; Zhang et al, 2020 ) and chronic restraint stress ( Ma et al, 2019 ) preparation of the GAD rat model. After 21 days of chronic stress stimulation, we found that GAD rats showed significant changes compared with the control group, such as decreased body weight growth rate ( Morris, 2019 ), reduced exploration behavior in the central area of the open field experiment ( Deacon, 2013 ), and significantly reduced exploration time to the open arm in the elevated cross maze ( Gasnas, 2021 ), and there were statistical differences, which proved that the physiological metabolism of the model group was disordered.…”
Section: Discussionmentioning
confidence: 99%